BRONCHUS AND LUNG CANCER INCIDENCE IN POPULATION LIVING AROUND THE FORMER URANIUM MAINING AND MILING SITES. Issue 1 (15th June 2018) - Chobanova, Nina; Ivanova, Kremena; Stojanovska, Zdenka; Atanasov, Trayan
Abstract: The indoor radon concentrations and lung cancer incidence in Eleshnitza village and Blagoevgrad district of Bulgaria were examined in the study reported here. The Eleshnitza was the second largest uranium mining and milling region of the country. The geometric mean of indoor radon concentration in Eleshnitza (465 Bq/m 3 ) was higher than the geometric mean of Blagoevgrad district (78 Bq/m 3 ). Retrospective analyses on lung cancer incidence, covering the period 1995–2012 have been shown the same trend. The results were suggestive of an existing relationship between the two variables. Possible effects attributable to age and gender on lung cancer incidence were examined and found to be significant.